Vocational Students’ Perspective Towards Digital Role-Play in Enhancing Speaking Skills - Pamungkas, Bagus Wahyu; Isnaini, Moh. Hasbullah (Universitas PGRI Madiun, 2024)
Speaking is a challenging skill for students to acquire in Indonesia. This study seeks to investigate the perspectives of vocational students regarding digital role-play as an opportunity for enhancing their speaking skills. This study employed a qualitative method, utilizing a case study as the research design. This study was carried out at SMKN 1 Singosari, Malang. Four participants were involved in the study, consisting of two students categorized as high-achieving and two categorized as low-achieving, majoring in welding engineering for the academic year 2024/2025. The research used semi-structured interviews to gather the data. The findings of this study indicate that digital role-play engages vocational students and enhances their excitement for learning to speak English. Through the use of digital role-play, vocational students believe they can enhance their vocabularies and immediately evaluate their problems, including mispronunciation. As a result, digital role-play serves as an advantageous technique that can be utilized, enabling vocational students to enhance their English speaking skills.